Missed Critical Value Callbacks Due to Middleware Flaws. (11th September 2019) - Altawallbeh, Ghaith; Senn, Christine; Rapp, Michael; Karger, Amy B
Abstract: A provider notified the laboratory of a missed sodium critical value notification on a patient; during further investigation, it was noted that the laboratory had missed a second sodium critical value notification several hours later on the same patient. The two missed critical callbacks occurred on different shifts with different technologists, pointing to a systematic issue. A thorough investigation was undertaken involving review of critical callback procedures, staff interviews, and retrospective data review to determine the etiology. It was confirmed that the middleware, Siemens Centralink, had captured and displayed the critical values for review. The Centralink display highlights rows with critical results in red for easy visual identification by the laboratory technologist, and a numerical code of "8" appears in the Normal Severity (NS) column as an additional cue. Upon discussion with involved laboratory staff, a supervisor noted that sodium consistently appears in the top row of the Siemens Centralink result screen when held for review. Our Siemens Centralink display was noted to have a blue bar that by default appears in the top row and was noted to obscure the red highlight and NS Flag that provides a visual cue to staff that it is a critical value. Therefore, we hypothesized that the sodium critical values were missed due to being obscured by the default blue bar, and hypothesized that they could be preferentially affected relative to other analytes due to sodium's default position in the top row when displayed. To investigate further, we pulled retrospective critical value callback data from our university hospitals for 2018. Our overall critical callback failure rates were 2.0%. When broken down by individual analyte, we found that 7.2% of sodium critical values were not called back to providers, whereas only 1.0% of potassium critical values were missed. Additionally, critical callback failure rates for hemoglobin were 0.1%; our hematology analyzer has a hard stop for all critical values, whereas the chemistry analyzer does not. In conclusion, we discovered that the default display on our Siemens Centralink middleware screen places a blue bar in the top row that obscures the visual cues associated with a critical value. Because sodium results are placed in the top row on the display screen, missed sodium critical callbacks occurred seven times more often than missed potassium callbacks. To remedy the issue, a blank row has been added to the display as the top row so that no clinical data are obscured by the default blue bar. Additionally, the very low critical callback failure rate on the hematology analyzer points to a need for a hard stop on the chemistry analyzer. We will prospectively monitor critical callback data for sodium to determine whether the display change improves sodium callback rates.